Amplop Misteri: Inovasi Baru Menginspirasi Menulis Narasi di Sekolah Dasar - Sarni, Sarni; Baderiah, Baderiah; Mirnawati, Mirnawati (Socratika: Journal of Progressive Education and Social Inquiry, 2025)
This study aims to improve the narrative writing skills of fourth grade students at MI Datok Sulaiman Palopo City using the Mystery Envelope (AMIS) media. The research was conducted in two cycles with steps of planning, implementation, observation, and reflection. The results showed that AMIS was effective in improving students' narrative writing skills. In cycle I, the average score of students' writing skills reached 73.8, with 77% of students achieving the learning objectives. In cycle II, the average score increased to 82.10, with all students achieving the learning objectives. Observation showed significant improvement in students' attendance, enthusiasm, and active participation. Student attendance in learning was excellent with an average score of 97.92, and student enthusiasm reached an average score of 84.17. Students' activeness in asking questions, answering questions, and expressing opinions also increased significantly. The use of AMIS created a more interactive and fun learning environment, with student engagement scores reaching 4 out of 4 and interaction and cooperation between students increasing to 3.5 out of 4. In conclusion, AMIS media is effective in improving students' narrative writing skills and creating a more interesting and participatory learning atmosphere. The findings suggest that AMIS is worthy of wider implementation in other schools as an innovative learning strategy to improve writing skills and student engagement.